Influência da escória de aciaria LD em argamassas de alto desempenho - Loureiro, Mayara Santos (2023)
The steel slag produced in the Lins Donawitz oxygen furnaces (BOF slag) is the main co-product of the process pig iron conversion into steel, reaching the generation mark of approximately 4.24 million tons per year in Brazil. Due it has expandability feature, the use of this waste product as a building material is limited, contributing to the formation of an environmental liability. On the other hand, there is an extensive demand for cementitious materials by the construction industry, of which it is known that, during their hydration process, they are affected by autogenous shrinkage. This is a phenomenon enhanced in materials with a low water/binder ratio, such as case of high-performance concretes and mortars. Therefore, this work investigated the technical feasibility of using BOF slag as a partial substitute for Portland cement in the production of highperformance mortars, in order to improve the properties, especially in the hardened state. For this purpose, an experimental program was developed where samples containing 5% and 10% of BOF slag and two w/b ratios (0.40 and 0.30) were dosed. The properties of consistency, kinetics of hydration reactions, porosity, mechanical resistance and dimensional variation of the compounds were evaluated. At the end of the study, it was possible to identify that the use of BOF slag as a supplementary cementitious material promoted a slight reduction in the consistency of the mixtures (up to 8% reduction in spreading) and an increased in porosity. Additionally, the BOF slag promoted a small extension in the induction period compared to the reference samples. However, the difference between the total heat released by the samples was not significant. Based on the compressive strength results and thermogravimetric analyses, it was observed that the values were equivalent between the reference mortars and those containing BOF slag, at the first ages. With the advancement of hydration, a greater gain in resistance was identified in the samples containing BOF slag, which could exceed the values of mixtures that do not use the residue. In the analysis of the dimensional variation, no significant alterations were verified in the results of the development of the autogenous shrinkage, furthermore an expansive action of the mortar containing BOF slag was not identified during the first 7 days of hydration. To sum up, with the results and analyzes carried out, it appears that the use of BOF slag in partial replacement of Portland clinker (in contents of up to 10%) proved to be a technically feasibility alternative.